Réponses

2013-01-05T17:49:23+01:00

1) lim en 0+ =infini  ---> A.V. x = 0 (à droite)

lim(infini) (x - lnx) = lim(infini) x (1 - lnx/x)  or lim0lnx/x = lim0 (1/x/1) = 0

                                et lim(infini) x (1 - lnx/x) = lim(infini) x = infini

2)lim0(ln(e^x + 1) = 2

   lim(-infini) ln(e^x + 1) = 0  y = 0 AH qd x tend vers  infini

    lim(infini) ln(e^x + 1) = infini

3) lim(+ ou -infini)(3(x-1)²/(x² +1) = 3 donc y = 3 AH.

   pas d'AV

j'ai supposé que l'exposant de x au dénominateur était 2.